A STUDY OF THE PUBLIC SPHERE (JURGEN HABERMAS) STATE HEGEMONY AND MEDIA CONSTRUCTION IN PUNKER ARRESTS IN ACEH - M Fakhran Al-Ramadan (English Didactic, 2021)
This study aims to explore how Aceh Punk community members construct their identity in relation to their historical identity development within the public sphere. The paper also traces back the development of Punk community in Aceh throughout Indonesia’s most important timeline. The article concludes with a brief comment and reflection on the arrest of Punkers in Aceh in 1965. The phenomenon also contests the freedom of expression of a certain subculture community against religious and traditional values adopted in the local community.